ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN DI INDONESIA - Suwaibah Suwaibah; Chenny Seftarita (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
AbstractThis study aims to determine the effect of macroeconomic variables on the composite stock price index in Indonesia. The macro variables used in this study are the BI Rate, the exchange rate, the money supply, world oil prices, and world gold prices. The analytical tool used is Autoregressive Distributed Lag (ARDL), with data processing using the software application Eviews 10, with secondary data consisting of monthly data. The results of this study indicate that in the short-term ralationship the variables that affect the joint stock price index are the money supply and the exchange rate, while in the long-term relationship the variables that affect the joint stock price index are the exchange rate and world il prices.  Keywords: Composite Stock Price Index, Macroeconomic Variable, ARDL